Relaxation and watching televised sports among older adults. Issue 2 (1st February 2016) - Ryu, Jungsu; Heo, Jinmoo
Abstract: This study shows a hierarchical regression model that investigates the relationship between watching televised sports and relaxation. Older adults ( N = 305) completed a self-report questionnaire to assess relaxation and media functions (entertainment, surveillance, correlation, and cultural transmission) when they watched televised sports. A hierarchical multiple regression analysis was conducted to examine the proportion of observed variance in relaxation explained by control and independent variables. The results indicated that the entertainment function and the correlation function were statistically significant predictors after controlling for gender and the number of days of watching televised sports. Entertainment function was the strongest predictor on experiencing relaxation for older adults when watching televised sports. The findings of this study add to the growing collection of research that suggests a positive relationship between casual leisure activities and relaxation among older adults.